Hybrid algorithm designed for handling remote integrity check mechanism over dynamic cloud environment - Arora, Shakti; Dalal, Surjeet (International Journal of Engineering and Technology, 2018)
Cloud computing is the becoming the architecture information technology of next generation. Cloud computing provides dynamic set of resources for different category of users. Remote access of resources is available on the pay per basis. Cloud is using the storage, computing, infrastructure services according to the requirements. Cloud manages all the user data at distributed level and provides reliability, flexibility and on demand services to user with very low cost. In Now days scenario cloud applications and data over the cloud machines are increasing day by day which indirectly invites different threats for the crucial and sensitive data on cloud. In this paper, we proposed a security model that will give the computational enhancements in different modules data. The different proposed modules: 1) key generation 2) access control strong encryption 4) remote integrity checks. The proposed model enhances t confidentiality, authentication and integrity of data. From the result analysis, it has been concluded that computation and communication overhead are minimized as compared to previous model with higher efficiency achieved.Â Â